FRI0492 Long-Term Safety and Efficacy of Canakinumab in Patients with Caps: Final Results from The Beta-Confident Registry. (15th July 2016) - Kuemmerle-Deschner, J.B.; Hoffman, H.; Hawkins, P.N.; van der Poll, T.; Walker, U.A.; Speziale, A.; Tilson, H.H.; Joubert, Y.
Abstract : Background: Cryopyrin-associated periodic syndrome (CAPS), is a rare autoinflammatory disease encompassing a spectrum of 3 phenotypes with an estimated population frequency ranging from 1–3 per million. 1, 2 The β -confident Registry (NCT01213641 ) is a multicenter, long-term, prospective, observational study with an enrollment period of 5 years (yrs) to monitor the long-term safety and efficacy of canakinumab (CAN) for CAPS. Here we report the overall final results. Objectives: The primary objective of the Registry was to monitor the safety of CAN, focusing on SAEs including serious infections, vertigo, malignancies and hypersensitivity reactions. Methods: Cumulative safety data were reported as incidence rate per 100 patient-yr (IR/100 pyr) from the enrollment of the first patient (November 2009) until end of study (December 2015). The registry protocol did not mandate any visits or procedures; however, all observed and reported AEs and SAEs or AEs potentially related to CAN were recorded. Efficacy was measured using physician global assessments (PGA). Results: Overall, 288 patients were enrolled at 39 sites across 13 countries with mean patient exposure duration of 3.6 yrs. Of these, 22 (8%) discontinued CAN: 5 due to AEs, 10 due to poor efficacy and patient preference; and 7 due to unknown reasons. The IR/100 pyr for overall AEs was 100.0. Among the phenotypes of CAPS, patients with familial cold autoinflammatory syndrome (FCAS) had the lowest IR/100 pyr (78.0) compared to patients with Muckle–Wells syndrome (MWS) (IR/100 pyr 113.4) and neonatal onset multisystem inflammatory disease (NOMID) (IR/100 pyr 119.0). The most common AEs were infections and infestations (IR/100 pyr, 39.1). Overall, 161 SAEs were reported by 86 patients (IR/100 pyr, 16.3), most commonly, infections (IR/100 pyr, 5.0). One death (metastatic rectal adenocarcinoma in 76-yr-old MWS patient) was reported. Of 23 patients that received pneumococcal vaccination (PPV), 15 (65%) reported local post-PPV injection site reactions, of which 5 were considered as serious. Based on PGA, 50% of patients had no disease activity, whereas most of the others experienced mild/moderate disease activity up to Month 48. Similarly, disease activity was absent or mild/moderate in patients with NLRP3 mutation negative CAPS (n=13) treated with CAN. Conclusions: The β-confident Registry is the largest CAPS cohort documented in a registry. This registry demonstrated that safety profile of canakinumab was consistent with previous findings and efficacy was sustained for more than 5 years. Canakinumab therapy was also effective in patients with NLRP3 mutation negative CAPS. References: Kuemmerle-Deschner JB, et al. Arthritis Res Ther. 2011;13(1):R34. Cuisset L, et al. Ann Rheum Dis. 2011;70(3):495–9. Disclosure of Interest: J. Kuemmerle-Deschner Grant/research support from: Novartis, Consultant for: Novartis, SOBI, Baxalta, H. Hoffman Grant/research support from: BMS, Consultant for: Novartis, SOBI, Regeneron, Speakers bureau: Novartis, P. Hawkins Grant/research support from: Novartis, T. van der Poll: None declared, U. Walker Consultant for: Novartis, A. Speziale Employee of: Novartis, H. Tilson Consultant for: Novartis, Y. Joubert Employee of: Novartis